As políticas de inclusão da rede municipal de ensino de Santo André (1989-2016): um estudo com base nas palavras-chave de Raymond Williams - Nascimento, Amanda Sousa Batista do (2022)
The object of study of this research are the regulatory frameworks of inclusive educational policies developed for the Municipal Education Network of Santo André, in the period between 1989 and 2016, with an emphasis on mapping a standard vocabulary of keywords, which we call inclusive repertoire. The question that guided the present study was thus elaborated: what are the inclusive repertoires of the Municipal Network of Santo André, and how did their origins come about? How were these concepts and keywords appropriated (or not) in the experiences of building curricular documents in the municipal network and became a collection with its own meaning? The general objective was to identify in the official documents produced by the Municipal Department of Education of Santo André in the period 1989-2016, how the incorporation of principles defined by the Constitution of the Federative Republic of Brazil (1988) took place, when it sustains the duty of the State in promote the good of all, without prejudice of origin, race, sex, color, age and any other forms of discrimination. The analysis of the documents was carried out by the perspective presented by Raymond Williams in the work Palavras-Chave: a vocabulary of culture and society, in which he claims that there are keywords that reproduce the ideology of a certain period, of a certain society, which suffer varied influences. , both from the dominant social elements in the period or geographic location, as from broader factors, coming from the political and economic scenarios, as well as influences from documents and international agencies linked to education. The first stage of the research consists of mapping the documents prepared by the Santo André municipal school system in parallel with the mapping of other experiences of inclusive education in other Brazilian cities and the identification and/or absence of a repertoire of keywords in them. The second stage of the research was based on a comparative study of keywords, responding to the research problem about the origin of this inclusive repertoire and presenting the characteristics of the experience of inclusive education in the municipal school system of Santo André. As a result, we came to the conclusion that there is indeed an inclusive repertoire, which runs through different experiences of inclusive education. With an emphasis on the municipal education network of Santo André, we highlight the following keywords that make up this repertoire: quality, education, democratization/democratic, social, management, policy, knowledge, evaluation. The research indicated that the origins of these concepts or keywords are the international and national educational policies themselves, influenced by the context of local policies and what Williams highlighted as a process of creation and circulation of specific meanings and values of a social formation. The presence or absence of certain keywords says a lot about the disputed territory that has become the educational field, in which government policies often take precedence over State policies.